Promoting the Development of Intercultural Competence in Higher Education Through Intercultural Learning Interventions - Maria Luisa Sierra-Huedo; Almudena Nevado-Llopis (Revista Electrónica Educare)
Introduction. This article analyses the impact of an intercultural learning intervention in a Spanish university post-European Higher Education Area implementation. Objective. Our research’s main objective consisted of measuring the development of intercultural competence in the first cohort of a Translation and Intercultural Communication bachelor’s degree in a Spanish university, before and after taking specific courses in intercultural studies and spending a study abroad semester. Methodology. A mixed methodology was implemented, in which the Intercultural Development Inventory (IDI) was used as a measuring instrument. Additionally, in-depth personal interviews were conducted to complement the data obtained. Results. The results of this study show that the programming and sequencing of specific courses, together with experiences abroad, contribute to the development of intercultural competence. Conclusions. More intercultural learning interventions are needed in higher education courses to develop and build an intercultural campus and educate global citizens. When applying intercultural learning interventions and intercultural methodologies, students develop their intercultural competence, a key competence for 21st-century graduates.